Cherokee materials, Floyd G. Lounsbury Papers - Albó, Xavier, 1934-; Lounsbury, Floyd Glenn; Zuidema, R. Tom, (Reiner Tom), 1927-; Farfán, José M. B.; Cook, Wiliam H.; Fenton, William N., (William Nelson), 1908-2005; Gillespie, John Douglas; Gillespie, John W.; Kurath, Gertrude Prokosch; Haas, Mary R. (Mary Rosamond), 1910-1996; Kilpatrick, Jack Frederich (1828)
The Cherokee matierals in the Lounsbury Papers include publications in the Cherokee syllabary dating back to 1828 in Series II. Of special interest are the recordings in Series VII, which include an account by Private John G. Burnett, an eyewitness to Cherokee removal, 1838-1839; a significant number of recordings of songs and dances made by Will West Long and Della Owl; Cherokee lessons by Robert Bushyhead and William Cook. The corresondence in Series I contains Harry Basehart's work on the Cherokee language, a Cherokee lullaby, FGL's work in Oklahoma on Cherokee; Committee on Linguistics and Psychology, Social Science Research Council, William Cook's manuscript "The Iroquoian Origins of the Cherokee language," William Fenton's work on Iroquois-Cherokee linguistic relations, John D. Gillespie's work on Cherokee grammar and dictionary, John W. Gillespie's work with Gertrude Kurath on Cherokee music, Mary Haas' recordings of Cherokee, Jack Kilpatrick's "Chronicles of Wolftown: Social documents of the North Carolina Cherokees, 1850-1862," and John Witthoft's materials on Cherokee herbal names and uses.